Influence of Source Shape on Semi-Airborne Transient Electromagnetic Surveys - Lei Liu; Jianghai Xie; Wentao Liu; Jianmei Zhou (Applied Sciences)
The semi-airborne transient electromagnetic (SATEM) method has garnered increasing attention and research interest due to its superior detection depth and high efficiency. Theoretically, the SATEM method employs a long straight grounded wire as its transmitter source; however, in practical applications, various source shapes emerge due to terrain constraints. This paper investigates the influence of source shape on SATEM data. A three-dimensional (3D) block model is established, and a model order reduction algorithm is applied to calculate the 3D spatial distribution of electromagnetic fields generated by both an ideal linear source and a curved source. Numerical simulation results reveal that: (1) in the early stage, maximum values of electric and magnetic fields near the source are distributed along the source shape; this influence diminishes with time, and at the late stage, the spatial electromagnetic field distributions generated by linear and curved sources converge, exhibiting similar patterns regardless of the source geometry; (2) the source shape primarily affects early responses in small-offset areas while having minimal influence on late responses in large-offset regions; (3) for deep detection applications conducted in large-offset areas, the influence of the source shape can be disregarded; however, for shallow detection with receivers positioned in small-offset regions, the source shape effects should be taken into consideration.